Penggunaan Alat Evaluasi Berbasis Quizizz Paper Mode Sebagai Upaya Peningkatan Hasil Belajar Materi Teks Pengumuman Dan Antusiasme Peserta Didik Kelas V Sekolah Dasar Negeri 1 Gedebeg Kabupaten Blora - Wahyu Utami; Panca Dewi Purwati; Yuli Ibawati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was motivated by class V students at SD Negeri 1 Gedebeg who seemed bored and not interested in implementing learning evaluations because evaluations were considered a burden and class teachers also felt that the learning evaluations given still seemed monotonous because usually the evaluations used were only written tests in the form of multiple choice questions and descriptions. This research aims to describe the use of quizizz paper mode-based evaluation tools in increasing the enthusiasm and learning outcomes of class V students at SD Negeri 1 Gedebeg, Blora Regency. This type of research is descriptive qualitative research with the research subjects being class V teachers and class V students with a total of 15 students. Data collection techniques in this research include tests, questionnaires, interviews, observation and documentation. The results of research using quizizz paper mode based evaluation tools can increase learning outcomes with learning success (class accuracy) of announcement text material using the quizizz paper mode platform by 82% and can increase student enthusiasm with indicators of response, attention, willingness, concentration and awareness to involve themselves in learning which on average has a very high level of enthusiasm.